An Online Intervention to Promote Mental Health and Wellbeing for Young Adults Whose Parents Have Mental Illness and/or Substance Use Problems: Theoretical Basis and Intervention Description - Reupert, Andrea; Bartholomew, Catherine; Cuff, Rose; Foster, Kim; Matar, Jodie; Maybery, Darryl J.; Pettenuzzo, Laura (Frontiers in Psychiatry, 2019)
The transition to adulthood can be a vulnerable period for certain population groups. In particular, young adults aged 18–25 years who have a parent with mental illness and/or substance use problems face increased risks to their mental health compared to same aged peers. Yet these young adults may not have access to age-appropriate, targeted interventions, nor engage with traditional face-to-face health services. To support this vulnerable group, services need to engage with them in environments where they are likely to seek help, such as the Internet. This paper describes the risk mechanisms for this group of young adults, and the theoretical and empirical basis, aims, features and content of a tailored online group intervention; mi.spot (mental illness: supportive, preventative, online, targeted). The participatory approach employed to design the intervention is described. This involved working collaboratively with stakeholders (i.e., young adults, clinicians, researchers and website developers). Implementation considerations and future research priorities for an online approach targeting this group of young adults conclude the paper.